Success Rate of Coronary Artery Bypass Grafting on Elderly Patients in Dr. Soetomo General Academic Hospital, Surabaya - Tombokan, Amelia Mathilda; Sembiring, Yan Efrata; Dharmadjati, Budi Baktijasa; Pribadi, Oky Revianto Sediono (Universitas Airlangga, 2024)
Highlights: CABG is the most performed cardiac surgery in Indonesia, and most patients undergoing this surgery are above 60 years old. CABG success rate is not significantly influenced solely by the patient's age but also by several perioperative characteristics such as gender, comorbidities, and other variables included in the calculation of EuroSCORE II. Abstract Introduction: Coronary artery disease (CAD) has caused more than a quarter of deaths in Indonesia and is found to be more prevalent in elderlies (â‰¥60 years old). Treatment options include coronary artery bypass grafting (CABG), the most-performed cardiac surgery in Indonesia. This study aimed to determine the short-term and one-year postoperative success, morbidity, and mortality rates with their causes in Dr. Soetomo General Academic Hospital, Surabaya. Methods: This was a cross-sectional retrospective study using secondary data obtained from 85 medical records of CABG patients aged â‰¥60 years old in the Department of Thoracic, Cardiac, and Vascular Surgery Dr. Soetomo General Academic Hospital, Surabaya, from January 2018 to December 2020. Aside from descriptive statistics, logistic regression was conducted to assess the relationship between EuroSCORE II and the success of CABG in elderly patients. A probability (p) value < 0.05 was considered significant. Results: Patients were mostly male in their sixties with a mean of 65.5 ± 4.9 years old, had three-vessel disease, and predicted mortality of 1.6%. The average number of grafts used was 3.3 ± 0.7, and the average length of hospital stay was 7.4 ± 2.4 days. The morbidity rate was 71.8%, with bleeding as the most common complication, a 17.6% mortality rate, and a success rate of 82.4% (short-term) and 80% (one-year postoperative). Higher EuroSCORE II was found to significantly decrease the probability of both short-term (prevalence ratio [PR], 0.766; 95% CI, 0.604-0.971; p = .028) and one-year postoperative success (PR, 0.787; 95% CI, 0.624-0.993; p = .044). Conclusion: Surgical success in elderly patients is influenced by many factors, and old age should not deter physicians from referring patients for CABG. Despite the ability of EuroSCORE II to predict surgical success, both short-term and one-year survival, on elderly patients, there is a need for holistic and locally validated scoring systems to both evaluate and predict surgical success due to the unique healthcare context of Indonesia.